Do smokers support smoke-free laws to help themselves quit smoking? Findings from a longitudinal study. Issue 3 (10th January 2014) - Nagelhout, Gera E; Zhuang, Yue-Lin; Gamst, Anthony; Zhu, Shu-Hong
Abstract : Background: A growing number of smokers support smoke-free laws. The theory of self-control provides one possible explanation for why smokers support laws that would restrict their own behaviour: the laws could serve as a self-control device for smokers who are trying to quit. Objective: To test the hypothesis that support for smoke-free laws predicts smoking cessation. Methods: We used longitudinal data (1999–2000) from a US national sample of adult smokers (n=6415) from the Current Population Survey, Tobacco Use Supplements. At baseline, smokers were asked whether they made a quit attempt in the past year. They were also asked whether they thought smoking should not be allowed in hospitals, indoor sporting events, indoor shopping malls, indoor work areas, restaurants, or bars and cocktail lounges. At 1-year follow-up, smokers were asked whether they had quit smoking. Findings: Smokers who supported smoke-free laws were more likely to have made a recent quit attempt. At 1-year follow-up, those who supported smoke-free laws in 4–6 venues were more likely to have quit smoking (14.8%) than smokers who supported smoke-free laws in 1–3 venues (10.6%) or smokers who supported smoke-free laws in none of the venues (8.0%). These differences were statistically significant in multivariate analyses controlling for demographics. Conclusions: Support for smoke-free laws among smokers correlates with past quit attempts and predicts future quitting. These findings are consistent with the hypothesis that some smokers support smoke-free laws because the laws could help them quit smoking.